The Influence of Entrepreneurship Education And Adversity Question on Entrepreneur Intention Through Entrepreneurial Attitude on Students in Jombang District - Nabilah, Zahidah Ismah; Rahayu, Wening Patmi; Maharani, Satia Nur (International Education Trend Issues, 2024)
Entrepreneurial intention is a person's encouragement in deciding what they will do and the realization is in the form of an attitude that is done. This study examines the direct and indirect effects of Entrepreneurship Education, Adversity Questions, and Entrepreneur Intention through Entrepreneurial Attitude. The sample of this research is students of private universities in Jombang Regency who have taken entrepreneurship courses such as STIE PGRI, Darul Ulum University, Hasyim'Asyari University, KH.A.Wahab Hasbullah University, PGRI University which amounted to 235 respondents. Data analysis used descriptive analysis, Structural equation model-partial least square (SEM-PLS). The results of this study found that there is a positive and significant effect of Entrepreneurship Education on Entrepreneurial Attitude, Adversity question on Entrepreneurial Attitude, and there is a positive and insignificant effect of Entrepreneurship Education on Entrepreneur Intention, there a positive and significant effect of Adversity Question on Entrepreneur Intention and there is no indirect effect of Entrepreneurship Education, on Entrepreneur Intention through Entrepreneurial Attitude. There is an indirect effect of the Adversity Question on Entrepreneur Intention through Entrepreneurial Attitude.